Mengidentifikasi Penyedia Layanan Logistik di Marketplace Studi Kasus di Cirebon Menggunakan Pendekatan Analisis Hirarki Proses (AHP) - Muhammad Aditya Ihsan Sidik; Dewi Laily Purnamasari; Yuningsi Yuningsi (Komunitas Dosen Indonesia, 2024)
In the digital era, marketplaces have become the primary platforms for MSMEs (Micro, Small, and Medium Enterprises) in Indonesia to increase their revenue. The operational success of a marketplace heavily relies on the performance of reliable logistics services, in addition to the quality of the products offered. This study utilizes the Analytic Hierarchy Process (AHP) method to identify the factors influencing the performance of logistics service providers in marketplaces and to evaluate their performance. The research population involves 341,240 people from Cirebon City and Regency, with a sample of 100 respondents selected through purposive sampling. The performance assessment of logistics services is based on key criteria, such as delivery speed, cost, and service quality, along with sub-criteria like order processing time and delivery estimate accuracy. Data were collected through an online questionnaire and evaluated across four logistics service providers: J&T Express, JNE, Shopee Xpress, and Si Cepat. The findings indicate that delivery timeliness is the primary criterion prioritized by consumers, followed by service quality and cost. Based on the evaluation, Si Cepat is rated as the best logistics service provider according to the overall criteria, followed by JNE, Shopee Xpress, and J&T Express. This study provides guidance for logistics service providers to enhance their service quality and assists consumers in choosing the most suitable logistics services based on their preferences and needs.